Emotion Regulation as an Adaptive Process in Multireligious Families: A Qualitative Study on Adolescents - Suci Lestari (Kuras Institute, 2026)
This study explores emotion regulation patterns among late adolescents (aged 18-21) from interfaith parental marriages in Bandar Lampung, Indonesia, where differing religious values and socialization practices create unique emotional challenges impacting identity formation and family harmony. Employing a qualitative case study approach, in depth interviews with three participants, observations, and document analysis were thematically analyzed using NVivo 12 Plus, with triangulation ensuring credibility. Findings highlight adaptive strategies including cognitive reappraisal, self calming techniques like deep breathing, goal directed behaviors to maintain academic focus, controlled emotional responses for family harmony, and acceptance of mixed emotions such as confusion and guilt, influenced by internal factors (emotional awareness, past experiences) and external supports (peers, open communication). These insights underscore the value of inclusive parenting in multireligious families to bolster emotional resilience and contribute to psychological literature on emotion socialization in diverse cultural contexts.